Multivariate optimization of dispersive liquid-liquid microextraction for the determination of paclobutrazol and triflumizole in water by GC-MS - Chormey, Dotse Selali; Karakus, Yesim; Karayaka, Sena; Ozsoyler, Cagla; Bozdogan, Abdurrezzak Emin; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2017)
A new analytical method based on dispersive liquid-liquid microextraction with gas chromatography mass spectrometry has been optimized for the simultaneous determination of paclobutrazol and triflumizole in tap water and wastewater samples. A two-level, full-factorial design that allowed the study of main effects and factor interactions was applied to analyze the influence on microextraction process by chloroform, ethanol, potassium iodide and hand shaking period. The extraction conditions selected were 200 mu L of chloroform, 3.0 mL of ethanol, 2.0 g of potassium iodide and 15 s of hand shaking. The limits of detection obtained for triflumizole and paclobutrazol under optimum conditions were 0.97 and 0.29 ng/mL, respectively. Calibration plots of both analytes were linear over a wide concentration range, and good precision was observed for replicate measurements. Applicability and accuracy of the method were determined by performing spiked recovery tests. Appreciable recovery results were obtained for municipal wastewater and matrix matching was used to obtain close to 100% recovery for tap water.
Keywords: dispersive liquid-liquid microextraction; factorial design; multivariate optimization; paclobutrazol; triflumizole; PESTICIDE-RESIDUES; GAS-CHROMATOGRAPHY; Chemistry